Respon Pengguna Facebook terhadap Tugas Matematika - Sitti Maesuri Patahuddin; Hasan Basri (Universitas Syiah Kuala, 2015)
This is a part of a larger study investigating the potential of Facebook for mathematics learning. This case study explored the responses of Facebook users towards opened and closed mathematical tasks posted on Facebook. In total, 149 Facebook users responded to the tasks resulting in 242 comments during a short period of time. All of the responses were downloaded and content analysis was utilised to identify patterns occurring within the responses. Virtual ethnographic study was also applied to further identify the demographical background of participants (education/professional background and locations). The results of this study suggests that opened mathematical tasks create broader opportunities for the Facebook users to express their mathematical ideas in different ways and attract richer mathematical interactions among the users than closed mathematical tasks. The nature of the task potentially shaped the types of responses from the Facebook users. This paper discusses some broad observations on the implications of the study as well as suggestions for future research.